Synthesis, characterization and mechanical study of polypropylene polymer based reinforced concrete with different admixture - Sarmast, Syed Mahmood Mohiuddin; Kunte, Anil; Roy, Aashis (Technium: Romanian Journal of Applied Sciences and Technology, 2022)
We have fabricated two different concrete based on polypropylene fibers with three different percentage admixture and water repellent dosages. The mortar mixtures were proportioned with cement to sand ratio of 1:3 and 1:4. The important FTIR peaks indicates that the presence of polypropylene fibers, and water repellent silicon in concrete mixture. The XRD spectra confirmed that the angle 2th value with corresponding planes are because of mainly tetrahedrally arranged silicate and octahedrally arrangement of aluminate groups in mixed concrete. The reinforced concretes were cast for the same flow level but different percentages of polypropylene fibers (0, 5, 10 & 15%) dosage. The mechanical study proves that the compressive strength and tensile strength of the concretes increases with increase in polypropylene based concrete mixtures up to 10 wt %. However, it is also noted that the admixture significantly enhances the mechanical strength and decreases the early shrinkage of the concrete.